Implementasi Eksekusi Uang Paksa (Dwangsom): Studi terhadap Putusan-putusan Hakim tentang Uang Paksa (Dwangsom) di Pengadilan Negeri Ponorogo - Munawir S.H. (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2015)
Ponorogo District Court is a court of first instance that handles many civil and criminal law cases. In handling civil law cases filed at the Ponorogo District Court, sometimes there are also demands for forced money / wangsom. From 2009 to 2013 based on the results of interviews with Mrs. Heny Trimira, deputy chairperson of the Ponorogo District Court there were 15 to 20 cases of default disputes in which there were also demands for forced money, but only 5 cases were granted. The reason why not all forced money claims are granted by the court is because in practice it is already difficult to enforce the main claim. Based on the five decisions sampled from 2009 to 2013, three decisions granted the main verdict and the award of dwangsom as a guarantee for the implementation of the main verdict. So that if you pay attention, even though the five decisions above have a dwangsom claim, not all of them were simultaneously granted by the panel of judges in the decision. So from the five decisions, with the granting of 3 decisions on the application for dowry, it proves that dowry is still relevant to be used as a guard so that the main decision is immediately implemented by the losing party.